On Market Integration and Liberalisation: Method and Application to Ethiopia. - Dercon, S (1995)
The article suggests further improvements in the methodology to analyse market integration. It provides corrections to and methodological extensions of recent work in this journal. It also presents a way of applying market integration techniques to the analysis of shocks such as market liberalization and war. The method is applied to the effects of liberalization and the end of the civil war on food markets in Ethiopia. The conclusion is that liberalization had important effects on the long-run and short-run integration of food markets.